1992
DOI: 10.1099/0022-1317-73-3-709
|View full text |Cite
|
Sign up to set email alerts
|

Infectious in vivo transcripts of a plum pox potyvirus full-length cDNA clone containing the cauliflower mosaic virus 35S RNA promoter

Abstract: A full-length cDNA clone of an aphid non-transmissible isolate of plum pox potyvirus (PPV) was rendered biologically active when placed under the control of the cauliflower mosaic virus 35S RNA promoter and the nopaline synthase polyadenylation signal. The cDNA was constructed so that the exact 5' end of the PPV RNA was present at the transcription initiation site.Inoculation of plasmid DNA onto Nicotiana benthamiana led to systemic infection, whereas local lesions were produced in Chenopodium amaranticolor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 20 publications
0
41
1
Order By: Relevance
“…The infectious full-length clone p35PPV-NAT of the non-aphid transmissible strain of PPV (Maiss et al, 1992) as well as wildtype virus isolates of TVMV (PV-0253, DSMZ, Germany), PVA (SCRI collection), PVY-O (SCRI collection), PPV-SK68 (Palkovics et al, 1993) and PVY-H (Thole et al, 1993) were used in the respective experiments.…”
Section: Viruses and Viral Full-length Clonesmentioning
confidence: 99%
See 1 more Smart Citation
“…The infectious full-length clone p35PPV-NAT of the non-aphid transmissible strain of PPV (Maiss et al, 1992) as well as wildtype virus isolates of TVMV (PV-0253, DSMZ, Germany), PVA (SCRI collection), PVY-O (SCRI collection), PPV-SK68 (Palkovics et al, 1993) and PVY-H (Thole et al, 1993) were used in the respective experiments.…”
Section: Viruses and Viral Full-length Clonesmentioning
confidence: 99%
“…A plasmid with a PPV-NAT/TVMV chimeric sequence was prepared by digesting a TVMV full-length clone (pXBS; Domier et al, 1986) with BamHI/EcoRI and cloning a 1748 bp fragment into pTrueBlue (Slilaty and Lebel, 1998) giving pTB_10T. After digestion of p35PPV-NAT (Maiss et al, 1992) with EcoRI/SacI, a 836 bp fragment was fused to the TVMV sequence of pTB_10T (pTB_10TP).…”
Section: Plasmid Construction and In Vitro Transcriptionmentioning
confidence: 99%
“…The constructs used in this study do not contain a polyadenylation signal downstream of the viral sequence, in contrast to the 35S-controlled clones constructed by Mori et al (1991), Commandeur et al (1991, MacFarlane et al (1992), Weber et al (1992 and Maiss et al (1992). Instead, the clones used in this study are linearized downstream of the viral sequence, thus preventing the synthesis of transcripts longer than the genome.…”
mentioning
confidence: 91%
“…Recently, the construction of directly infectious cDNA clones of brome mosaic virus RNAs 1, 2 and 3 (Mori et al, 1991), beet necrotic yellow vein virus RNAs 3 and 4 (Commandeur et al, 1991), pea early browning virus RNAs 1 and 2 (MacFarlane et al, 1992), tomato mosaic virus RNA (Weber et al, 1992) and plum pox virus RNA (Maiss et al, 1992) have been reported. These constructs make use of the cauliflower mosaic virus (CaMV) 35S promoter sequence linked to the 5' ends of the viral cDNAs to generate infectious transcripts in the plant.…”
mentioning
confidence: 99%
“…genomic cDNAs of several picorna-like plant viruses have been reported: CPMV (Vos et al, 1988), tobacco vein mottling virus (TVMV, Domier et al, 1989) and plum pox potyvirus (PPV, Riechmann et al, 1990;Maiss et al, 1992), but no infectious transcripts corresponding to genomic RNA of nepoviruses have so far been described. Here, we report the construction of clones containing the full-length cDNA of GFLV (isolate F13) RNA1 and -2 under the control of bacteriophage T3 or T7 RNA polymerase promoters.…”
Section: Introductionmentioning
confidence: 99%